PENGARUH KOMITE AUDIT, AUDIT INTERNAL, DAN WHISTLEBLOWING SYSTEM TERHADAP PENCEGAHAN KECURANGAN (FRAUD) - Agus Sumanto; Aditya Irsyad Zuhdi (Jurnal Ilmiah Akuntansi, 2026)
In the context of corporate governance, fraud represents a critical issue as it can cause substantial losses to companies, shareholders, and the wider public. Numerous cases in Indonesia, including asset misappropriation, financial statement manipulation, and corruption, indicate weaknesses in internal control systems. This study aims to examine the influence of the Audit Committee, Internal Audit, and the Whistleblowing System on fraud prevention in companies listed on the Indonesia Stock Exchange (IDX). The Audit Committee plays a key role in ensuring the accountability and transparency of financial reporting, while internal audit evaluates the effectiveness of operational procedures and internal controls. Meanwhile, the Whistleblowing System serves as an early detection mechanism that promotes a culture of integrity within organizations. The data used in this study were obtained from companies’ annual reports for the 2022–2024 period, with samples selected using purposive sampling based on the disclosure of corporate governance information. Data analysis was conducted using descriptive statistics and quantitative hypothesis testing. The results indicate that the Audit Committee, Internal Audit, and the Whistleblowing System have a significant effect on fraud prevention, both partially and simultaneously. These findings suggest that the more effectively these corporate governance mechanisms are implemented, the greater the company’s ability to reduce the risk of fraud..